Job Scheduling Considering Both Mental Fatigue and Boredom - Jahandideh, Sina (Université d'Ottawa / University of Ottawa, 2012)
Numerous aspects of job scheduling in manufacturing systems have been the focus of several studies in the past decades. However, human factors in manufacturing systems such as workers’ mental conditions are still neglected issues and have not received adequate attentions. Job boredom and mental fatigue are both aspects of workers’ mental condition. They affect work performances by increasing sick leave duration and decreasing work productivity. On the other hand, job rotation could be an alternative strategy to cope with such human issues at work. The benefits of job rotation for both employees and firms have been widely recognized in the literature. Although some studies found job rotation as a means to reduce workers' physical work-related traumas, they did not consider the effect of variable mental conditions on workers. Despite the proven importance of boredom and mental fatigue at the workplace, they have not been a combined precise objective of any job rotation problem in current literature. The study of mental conditions proposed in this paper attempts to extend the previous works by addressing new methods and developing a feasible solution to increase manufacturing productivity. A new job scheduling program has been designed specifically which combines a new job rotation model and a job assignment method.
Keywords: job scheduling; Mental Fatigue; Boredom; AHP; Job Assignment; Manufacturing System; job rotation; manufacturing productivity